2002
DOI: 10.5713/ajas.2002.55
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Value of Sugarcane Stalk for Cattle

Abstract: A metabolism trial with four castrated male Brahman cattle, average body weight 320 kg, was conducted in order to determine the nutritive value of chopped sugarcane stalk (CSS) for the establishment of feeding strategy in the dry season in Northeast Thailand. Animals were subjected to the following four dietary treatments: Treatment 1; 100% of CSS, Treatment 2; 70% of CSS and 30% of commercial complete feed (TMR), Treatment 3; 40% of CSS and 60% of TMR, and Treatment 4; 100% of TMR. The average CP, ether extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…In dairy cattle trial, Wanapat et al (1999) reported that feeding sugarcane tops with ureatreated rice straw was improved feed intake and nutrient digestion in dairy cattle. Similar resulted with Kawashima et al (2002a) who found that chopped sugarcane tops improved energy supply when compared with rice straw in diary cows. There is, however, very few literature focusing on alternative way to use sugarcane-tops as ruminant feeds.…”
Section: Introductionsupporting
confidence: 79%
“…In dairy cattle trial, Wanapat et al (1999) reported that feeding sugarcane tops with ureatreated rice straw was improved feed intake and nutrient digestion in dairy cattle. Similar resulted with Kawashima et al (2002a) who found that chopped sugarcane tops improved energy supply when compared with rice straw in diary cows. There is, however, very few literature focusing on alternative way to use sugarcane-tops as ruminant feeds.…”
Section: Introductionsupporting
confidence: 79%
“…In an attempt to evaluate sugarcane as a feed crop, Mizushima and Kobayashi (1977) argued that the feed composition of sugarcane is not very different from that of maize. Kawashima et al. (2002) suggested that if supplemented properly, sugarcane stalks could be used as roughage for cattle in the dry season in tropical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Without mentioning the common practice of feeding tops, which occurs in many parts of the world (Gendley et al. 2003), the whole crops are used as a valuable source of feed during drought in, for example, Thailand (Kawashima et al. 2002) and Cuba (Rodríguez et al.…”
Section: Introductionmentioning
confidence: 99%
“…Their byproducts, e.g. sugarcane top, bagasse, and molasses, are also commonly used to feed ruminants in these regions, while sugarcane stalks and whole sugarcane may also be used as feed (Kawashima et al 2002a, Kawashima et al 2002b, Kawashima et al 2003, Martin 1997, Pate et al 2002, Suzuki et al 2010, Suzuki et al 2014). Developing varieties with higher abiotic stress tolerance, regrowth ability, or nutritive value will enhance the utility of sugarcane as feed.…”
Section: Introductionmentioning
confidence: 99%